Yield of gene Xpert in diagnosing patients with pleural tuberculosis presenting to a tertiary care hospital - Awais Aslam; Istikhar Ali Sajjad; Abdul Wajid Khan; Hafiz Muhammad Taha Waqas; Zara Saleem; Hina Imtiaz (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Pleural tuberculosis is a common type of extrapulmonary tuberculosis and remains a common problem for pulmonologists. Early detection of tuberculosis is a global priority for TB control. Gene Xpert is a real-time PCR, which can reveal Mycobacterium tuberculosis within 2 hours. This study will bridge the gap and help the pulmonologist for deciding on the use of Gene Xpert as diagnostic tool for pleural tuberculosis. Our objective is to find the frequency of positive Gene Xpert among patients of pleural tuberculosis presenting to tertiary care hospital. METHODOLOGY: A Cross-sectional study was conducted in the Department of Pulmonology, Aziz Fatima Hospital, Faisalabad from 26 February 2022 to 25 March 2022. Total 187 patients ages between 15-80 years having pleural tuberculosis diagnosed during last 6 months were included in the study. Patients already taking anti-tuberculosis therapy were excluded. Pleural fluid was processed in Aziz Fatima Hospital, Faisalabad laboratory for Gene Xpert immediately. Reports were collected next day and noted in the proforma. Positive Gene Xpert as per operational definition. Data was stratified for variables like age, gender, comorbidities (like diabetes mellitus, and smoking status). Chi-square test was applied taking p-value ≤ 0.05 as significant. RESULTS: Out of 187 patients, mean age was 43.71±14.93 years. 95(50.8%) patients were male and 92(49.2%) patients were females. Positive Gene Xpert was found in 49(26.2%) patients. Out of 72 diabetic patients, 23(31.9%) patients had positive Gene Xpert and out of 115 non-diabetic patients, 26(22.6%) patients had positive Gene Xpert with p-value = 0.158. Out of 82 smoker patients, 27(32.9%) had positive Gene Xpert and out of 105 non-smoker, 22(21%) had positive Gene Xpert with p-value=0.065. CONCLUSION: Gene Xpert can be used as a reliable investigation for detection of pleural tuberculosis and timely initiation of treatment.